2005
DOI: 10.1002/esp.1247
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic enhancement in wildfire‐affected soil and its potential for sediment‐source ascription

Abstract: Intense rainfall following wildfire can cause substantial soil and sediment redistribution. With concern for the increasing magnitude and frequency of wildfire events, research needs to focus on hydrogeomorphological impacts of fire, particularly downstream fluxes of sediment and nutrients. Here, we investigate variation in magnetic enhancement of soil by fire in burnt eucalypt forest slopes to explore its potential as a post-fire sediment tracer. Lowfrequency magnetic susceptibility values (χ χ χ χ χ lf

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 32 publications
4
46
1
2
Order By: Relevance
“…In addition, these results suggest that the common practice of sieving to < 63 µm is likely to be unsuitable in regions such as the Karoo due to the very different relationships between tracers in the < 32 µm and 32 -63 µm fractions of soils and sediment. These findings support the findings of Maher (1998) and Blake et al (2006) who also showed that the ingrowth of secondary minerals during soil formation occurs primarily in fine soil particle sizes. To date we do not know the rate at which such in-growth occurs and whether significant changes occur over relatively short periods of time.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, these results suggest that the common practice of sieving to < 63 µm is likely to be unsuitable in regions such as the Karoo due to the very different relationships between tracers in the < 32 µm and 32 -63 µm fractions of soils and sediment. These findings support the findings of Maher (1998) and Blake et al (2006) who also showed that the ingrowth of secondary minerals during soil formation occurs primarily in fine soil particle sizes. To date we do not know the rate at which such in-growth occurs and whether significant changes occur over relatively short periods of time.…”
Section: Discussionsupporting
confidence: 91%
“…Magnetic signatures have been shown to be strongly affected by sediment particle size, introducing additional uncertainty to their use (Maher 1998;Blake et al 2006). Therefore, there is a requirement to separate biogenic, diagenetic and particle size effects for the correct interpretation of the stability of signatures in deposited sediment.…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggest that it may therefore be possible to reconstruct the long-term patterning of the degree of soil heating and thus infer past fire severities over a landscape by determining the spatially heterogeneous accumulation of thermally produced iron oxides in soils. The feasibility of such an approach is supported to some degree by results obtained in a parallel, independent study by Blake et al (2005), who used magnetic enhancement to determine the degree of soil heating under different fire severities in Australian Eucalypt forest.…”
Section: New Insightsmentioning
confidence: 99%
“…While these secondary processes may contribute to the ability to discriminate between sources, they may also result in post-depositional diagenesis which can obscure the linkage between the source and sediments. In addition, mineral magnetic properties have been shown to discriminate soil burned at different severities as well as unburned areas, however, recent research by Blake et al (2006) demonstrated that there was a lack of dimensionality in the data that limits their use in sediment fingerprinting (also see Smith et al 2013). Particle-size also exhibits a strong influence on the magnetic properties of sediment and needs to be taken into consideration in the characterization and interpretation of these properties (Oldfield and Yu 1994;Hatfield and Maher 2009).…”
Section: Geochemical Propertiesmentioning
confidence: 99%
“…Particle-size also exhibits a strong influence on the magnetic properties of sediment and needs to be taken into consideration in the characterization and interpretation of these properties (Oldfield and Yu 1994;Hatfield and Maher 2009). In many cases the relationship between particle size and measures of mineral magnetic properties is complex (Foster et al 1998;Blake et al 2006;Oldfield et al 2009) and this complexity can make it difficult to discriminate between sources and make comparisons between sources and sediments as a result of differences in particle size distributions.…”
Section: Geochemical Propertiesmentioning
confidence: 99%